Cytotoxicity and Antioxidant Activity of Extractives from Mirabilis jalapa (Stamford Journal of Pharmaceutical Sciences, 2009)
The petroleum ether, chloroform and methanol crude extracts of the two different plant parts (leaves and bark) of Mirabilis jalapa (Nyctaginaceae) were screened for cytotoxicity by brine shrimp lethality bioassay and the crude methanol extract of the bark was screened for antioxidant activity using the 1, 1-diphenyl-2- picrylhydrazyl-hydrate (DPPH) free radical scavenging assay. The petroleum ether extract of the bark showed significant cytotoxic activity with the LC50 value 8.12 μg/ml compared to vincristine sulphate (LC50 0.33 μg/ml). On the other hand, the methanol crude extract of the bark showed mild antioxidant activity with the IC50 value 598.02 μg/ml compared to ascorbic acid (IC50 70.985 μg/ml). Above results suggest moderate cytotoxic and antioxidant activity of the extract. Key Words: Mirabilis jalapa, Nyctaginaceae, Cytotoxicity, DPPH, Antioxidant.      doi:10.3329/sjps.v1i1.1814 S. J. Pharm. Sci. 1(1&2): 85-88